Recent advances in the development of aryl-based foldamers. - Saraogi, I; Hamilton, A (2009)
In recent years, significant effort has gone into making synthetic oligomers that can attain well-defined conformations analogous to the folding of biomolecules. The diversity of the structural building blocks ranges from peptidic and other aliphatic repeat units to aromatic ones, which do not have a natural counterpart. In this critical review, we will focus on the developments in aromatic foldamers in the last two years and their potential applications. This review will be of interest to people working on the structural and functional mimicry of biomolecules and will, we hope, stimulate further research into novel applications (149 references).